2022
DOI: 10.1111/trf.17090
|View full text |Cite
|
Sign up to set email alerts
|

Non‐cryopreserved peripheral blood stem cells as a safe and effective alternative for autologous transplantation in multiple myeloma

Abstract: Background: Autologous stem cell transplantation is the standard procedure for multiple myeloma and the grafts are usually cryopreserved. Previous studies reported advantages in the use of fresh peripheral blood stem cells (PBSC) autotransplantation compared to cryopreservation of the grafts. This study compared the transplant-related outcomes of two graft preservation methods: fresh storage (4°C/72 h) and cryopreservation (À80°C).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Our ASCT cases took longer in neutrophil recovery than those reported in previous studies [7, 9, 12, 13, 20, 21]. One possible reason is that our study concerned only patients with haematological malignancies but without solid tumors and autoimmune disorders.…”
Section: Discussionmentioning
confidence: 75%
“…Our ASCT cases took longer in neutrophil recovery than those reported in previous studies [7, 9, 12, 13, 20, 21]. One possible reason is that our study concerned only patients with haematological malignancies but without solid tumors and autoimmune disorders.…”
Section: Discussionmentioning
confidence: 75%
“…Several studies highlight the benefits of using fresh autologous stem cell products over cryopreserved ones for transplantation. For example, fresh products show faster engraftment with a lower incidence of neutropenia than cryopreserved products [18][19][20]. Furthermore, cryopreservation causes physiological changes in stem cell products, including cell aggregation [19].…”
Section: Discussionmentioning
confidence: 99%
“…For example, fresh products show faster engraftment with a lower incidence of neutropenia than cryopreserved products [18][19][20]. Furthermore, cryopreservation causes physiological changes in stem cell products, including cell aggregation [19]. In the majority of studies, the duration of fresh hypothermal storage is 48-72 hours for myeloma and lymphoma patients, indicating the potential benefits of extending the shelf life of fresh PBHSCs products [20].…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow (BM) is an alternate source of hepatocytes in the context of liver damage [ 148 151 ]. Previous research has shown that BM can generate a range of adult stem cells that express biomarkers for non-haematopoietic progenitor cells [ 152 154 ]. Although they may produce hepatocytes under tissue stress, BM cells have little impact on parenchymal replenishment in liver damage [ 27 , 155 158 ].…”
Section: Diverse Cell Sources and Therapeutic Sites For Cell Therapymentioning
confidence: 99%